lncRNA Ubr5 promotes BMSCs apoptosis and inhibits their proliferation and osteogenic differentiation in weightless bone loss - Wang, Dong; Gao, Yuan; Tan, Yingjun; Li, Na; Li, Xi; Li, Jiaxiang; Pan, Yikai; Zhao, Xingcheng; Yan, Ming; Wang, Yongchun (Frontiers in Cell and Developmental Biology, 2025)
BackgroundWeightless bone loss is a common pathological phenomenon in weightless environments, yet its specific molecular mechanism remain incompletely elucidated. The aim of this study was to systematically investigate the differential expression profiles of mRNAs and long noncoding RNAs (lncRNAs) to explore the molecular pathogenesis underlying weightless bone loss.MethodsTranscriptome sequencing was performed on bone marrow mesenchymal stem cell (BMSCs) samples from the Ground control group and simulated microgravity (SMG) group using Illumina technology. Using the DESeq2 algorithm, we accurately identify and analyzed the differentially expressed genes (DEGs). Subsequently, the molecular functions and signaling pathways enriched by DEG were comprehensively analyzed by GO and KEGG. In addition, by constructing lncRNA-mRNA coexpression network, this study screened and verified key lncRNAs as potential genes to further explore their role in the occurrence and development of weightless bone loss.ResultsA total of 215 differentially expressed lncRNAs (DElncRNAs) and 381 differentially expressed mRNAs (DEmRNAs) were identified, in the SMG group. DEmRNAs were primarily involved in the cell response to mechanical stimulation, microtubule motility and TNF signaling pathway. Meanwhile, DElncRNAs are significantly enriched in cell differentiation, fatty acid metabolic process and biosynthesis of amino acids. In addition, the expression levels of related lncRNAs and mRNAs in weightless bone loss were verified via qRT-PCR. lncRNA-mRNA coexpression network found that lncRNA Ubr5 closely related to osteoblast proliferation and differentiation. Further experimental results revealed that knocking down lncRNA Ubr5 can promote the apoptosis of BMSCs and inhibit their proliferation and osteogenic differentiation.ConclusionThis study revealed the molecular pathogenesis of weightless bone loss, identified lncRNA Ubr5 as a potential intervention target, and provided an important scientific basis and strategic guidance for the prevention and treatment of weightless bone loss.